(untitled) (Revista INTEREDU11, 2021)
This article aims to show the relationship that a public policy at an educational level has with the practices of structural racism that the Colombian state has. For this purpose, a policy was chosen that could become a clear example of the omission with which the state works against the demands of the black, Afro-Colombian, Raizal and Palenqueras communities. This policy is the CEA, which appears in the national act 1122 of 1998, in response to the demands of the communities exposed in law 70 of 1993. This article will begin with a normative review of the public policy, evaluating its status according from a vast report delivered by the Ministry of the Interior, the previous year, evidencing the existence of racialized public policies and culminating in a series of proposals aiming change that subvert this situation and allow the fulfillment of affirmative actions within the Colombian educational system.